Efficacy of endoscopic repair for CSF otorrhoea in children with recurrent meningitis due to incomplete partition type 1. (August 2022) - Mittal, Yash; Chappity, Preetam; Grover, Mohnish; Gupta, Gaurav; Pradhan, Pradeep; Parida, Pradipta Kumar; Mishra, Abhijeet
Abstract: Objective: To review the efficacy of endoscopic management with or without cochlear implantation in a pediatric population presenting with recurrent meningitis due to inner ear incomplete partition type 1 (IP-1). Materials and methods: A multicentric report of 6 patients with a history of recurrent meningitis due to IP-1 was done. Radiological evaluation was performed to confirm the diagnosis. Transcanal endoscopic repair of the defect was performed in 3 cases, 2 cases underwent endoscope-assisted repair followed by cochlear implantation in the contralateral ear later, and 1 patient underwent endoscopic repair along with simultaneous cochlear implantation. Results: Radiology confirmed the diagnosis and identified the site of the leak. A leak was detected in all cases from the stapes footplate. Two patients with unilateral deformity had a CSF-filled cyst protruding through a defect in the stapes footplate, and the rest of the four had a high flow CSF leak from the footplate. Five patients who underwent repair have had no further episodes of meningitis. One patient who received simultaneous implantation and repair developed postoperative meningitis managed successfully with antibiotics. Conclusion: Hearing loss due to inner ear deformity can be easily missed as a cause for recurrent meningitis, especially if unilateral. A high index of suspicion, audiological screening and radiology are essential to clinch the diagnosis. In such cases, a pure endoscopic or endoscopic assisted transcanal approach to repair CSF otorrhoea is an effective alternative to more radical procedures like subtotal petrosectomy with obliteration. In patients with bilateral profound hearing loss, simultaneous cochlear implantation and repair of the defect can be performed successfully. Highlights: Incomplete partition defect type1 (IP-1 ) can be a rare cause of otogenic meningitis. Endoscopic or endoscopic-assisted transcanal techniques are efficacious in repairing CSF otorrhoea in these cases. Simultaneous repair and implantation can be performed with good outcomes.